Edukasi Tanaman Obat Berdasarkan Kajian Etnobotani dan Thibbun Nabawi di MI Nurul Huda Penggung Boyolali - Rini Verary Shanthi; Wildan Nur Hidayat (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2022)
This study aims to determine and analyze medicinal plant education based on ethnobotanical and thibbun Nabawi studies at MI Nurul Huda Penggung Boyolali. This type of research is qualitative research using a descriptive approach. The method in this research is by taking data using interviews, observation and documentation. The location of this research is MI Nurul Huda Penggung, Boyolali Regency, Central Java Indonesia. The analysis used in this research includes: Data Reduction, Data Display, Conclusion Drawing and verification. The results of this study indicate that the medicinal plant education program carried out at MI Nurul Huda Boyolali aims to introduce, foster and increase children's knowledge, knowledge and interest in medicinal plants. plants that are socialized to students, are plants that are often found in homes planted in the madrasah environment include 18 types of plants such as: Jahe, Bawang Putih, Bawang Merah, Kunyit Putih, Kunyit Kuning, Lidah Buaya, Kencur, Jeruk Nipis, Pepaya, Sirih Merah, Jahe Merah, Adas, Kapulaga, Jeruk Purut, Dlingo, Lempuyang, Bawang Lanang, dan Sirsak. The success of this implementation can be due to supporting factors such as: 1) The service method used was effective enough to attract students' interest; 2) The school is very cooperative and helps prepare a conducive implementation place such as courtyards, classrooms and complete lcd projector and loudspeaker facilities; 3) MI Nurul Huda students are very proactive and enthusiastic in doing the assignments given; 4) The speaker as a resource person is very good at the topic given in the service; 5) The abundance of biological resources that are the raw material for TOGA planting education.